A Political Companion to Herman Melville - Frank, Jason A. (Book collections on Project MUSE., 2013)
Herman Melville is widely considered to be one of America's greatest authors, and countless literary theorists and critics have studied his life and work. However, political theorists have tended to avoid Melville, turning rather to such contemporaries as Ralph Waldo Emerson and Henry David Thoreau to understand the political thought of the American Renaissance. While Melville was not an activist in the traditional sense and his philosophy is notoriously difficult to categorize, his work is nevertheless deeply political in its own right. As editor Jason Frank notes in his introduction to A Pol.